PERAN CORPORATE SOCIAL RESPONSIBILITY PT BUMI PERSADA PERMAI DALAM PEMBERDAYAAN MASYARAKAT (STUDI DI DESA TELANG KEC. BAYUNG LENCIR) - Sulistiawan, Dexxi; Isma, Asad; Kurniawan, Bambang (Program Studi Manajemen Keuangan Syariah, 2024)
This study aims to determine the role of the PT Bumi Persada Permai unit Selaro CSR program in community empowerment in the core village. The results of this study are epected to be used as input for companies, communities, local government, science and assist CSR practition in implementing community empowerment-based CSR programs. This research is a qualitative research by conducting direct research in the field through observation, interviews, and documentation. By taking the research object in Teang Village as one of the core target village of PT Bumi Persada Permai district/unit Searo. The results of research and discussion show that the CSR program carried out by the company does not play a role in communty empowerment in Telang Village and has not been able to improve the quaity of life o the community. This was discovered because there were programs that did not work in strengthening the economy in the Village community Telang.